Digital signal processing demystified - Broesch, James D. (Engineering mentor series)
James D. Broesch is a staff engineer for General Atomics, where he is responsible for the design and development of several advanced control systems used on fusion control programs. He also teaches classes in signal processing and hardware design at the University of California-San Diego.